Hubungan Antara Kepercayaan Diri Dengan Keterampilan Berkomunikasi Serta Implikasi Terhadap Bimbingan Dan Konseling di SMPN 15 Bekasi - Denissa Rahmi; Solihatun; Kasmanah (CV Putra Publisher, 2025)
This study aims to analyze the relationship between self-confidence and communication skills. The type of research used is descriptive quantitative research. The population of this study were students of class VIII SMPN 15 Bekasi, the population was 1,095 and the number of samples of this study was 184 students. The sampling technique used the Simple random sampling technique. The instrument trial was carried out by testing the validity using person product moment, valid items of self-confidence variables were 31 and valid items of communication skills variables were 29. The calculation of reliability using Alpha Cronbach, obtained r count> r table self-confidence of 0.886> 0.6, communication skills obtained r count> r table 0.883> 0.6 then declared reliable. The prerequisite test for data analysis used was the Kolmogorov Smirnov normality test by obtaining results of 0.855 and 0.920 then declared dual normal, then the linearity test was obtained the result of 0.000 then the data was declared linear. Hypothesis testing was carried out using product moment correlation obtained r = 0.633. Based on the research results, it can be concluded that there is a relationship between self-confidence and communication skills in class VIII students at SMPN 15 Bekasi.